Endometriosis: A Hormonal Approach - Gürateş, Bilgin; Sapmaz, Ekrem; Kiliç, Gökhan; Çelik, Hüsnü (My University, 2003)
Estrogen is an extremely potent mitogen for endometrium and endometriosis. The product of a single gene named aromatase, synthesizes estrogen. Aromatase is the rate-limiting enzyme for the conversion of C19 steroids to estrogens in a number of human tissues including the ovary. Additionally, the pathologic estrogen-dependent tissues such as breast cancer and endometriosis also produce significant levels of aromatase and local estrogen. The clinical significance of local aromatase activity in endometriotic tissue was exemplified recently by the successful use of an aromatase inhibitor to treat an unusually aggressive and resistant case of recurrent postmenopausal endometriosis. Therefore, aberrant aromatase expression in endometriotic tissue, in contrast to eutopic endometrium, accounts for local biosynthesis of estrogen that promotes the growth of these lesions. The potent estrogen, estradiol is metabolized and thus inactivated by an enzyme termed 17?-hydroxysteroid dehydrogenase (HSD) type 2. Progesterone action is mediated by its receptor subtypes, progesterone receptor (PR)-A and PR-B. Progesterone, on the other hand, inhibits the mitogenic action of estrogen on endometrium and enhances differentiation. These antiproliferative and differentiative effects of progesterone are less pronounced on endometriotic tissue compared with endometrium. Thus, endometriosis is, at least in part, resistant to progesterone action. A number of abnormalities has been found in the expression of aromatase, 17?-HSD type 2 and PR-B/PR-A ratio in endometriotic tissue. These abnormalities and their functional consequences will be discussed in this review article.
Hormonal Açidan Endometriyozis
Keywords: 17?-hydroxysteroid Dehydrogenase type 2; Aromatase; Aromatase Inhibitors; Endometriosis; Endometrium; Estradiol; Estrogen; Estrogen Biosynthesis; Estrogen metabolism; Estrone; Progesterone; Progesterone receptors